The Arctic picoeukaryote Micromonas pusilla benefits from ocean acidification under constant and dynamic light - E. White; C. J. M. Hoppe; B. Rost; B. Rost (Biogeosciences, 2020)
Compared to the rest of the globe, the Arctic Ocean is affected disproportionately by climate change. Despite these fast environmental changes, we currently know little about the effects of ocean acidification (OA) on marine key species in this area. Moreover, the existing studies typically test the effects of OA under constant, hence artificial, light fields. In this study, the abundant Arctic picoeukaryote Micromonas pusilla was acclimated to current (400 µatm) and future (1000 µatm) pCO2 levels under a constant as well as a dynamic light, simulating more realistic light fields as experienced in the upper mixed layer. To describe and understand the responses to these drivers, growth, particulate organic carbon (POC) production, elemental composition, photophysiology and reactive oxygen species (ROS) production were analysed. M. pusilla was able to benefit from OA on various scales, ranging from an increase in growth rates to enhanced photosynthetic capacity, irrespective of the light regime. These beneficial effects were, however, not reflected in the POC production rates, which can be explained by energy partitioning towards cell division rather than biomass build-up. In the dynamic light regime, M. pusilla was able to optimize its photophysiology for effective light usage during both low- and high-light periods. This photoacclimative response, which was achieved by modifications to photosystem II (PSII), imposed high metabolic costs leading to a reduction in growth and POC production rates when compared to constant light. There were no significant interactions observed between dynamic light and OA, indicating that M. pusilla is able to maintain effective photoacclimation without increased photoinactivation under high pCO2. Based on these findings, M. pusilla is likely to cope well with future conditions in the Arctic Ocean.